2015
DOI: 10.1093/eurpub/ckv111
|View full text |Cite|
|
Sign up to set email alerts
|

What causes health inequality? A systematic review on the relative importance of social causation and health selection

Abstract: The review highlights the fact that the causal mechanisms behind health inequalities are dependent on whether or not the dimension being analyzed closely reflects labor market success. Additionally, further research should strive to improve the statistical modeling of causality, as this might influence the conclusions drawn regarding the relative importance of health selection and social causation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
141
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(157 citation statements)
references
References 65 publications
4
141
1
6
Order By: Relevance
“…For emotional support given and social activity, we found some evidence for a decrease in inequalities over the course of old age. While it is important to note that, on the basis of our analyses, we cannot draw conclusions about whether socioeconomic conditions caused initial inequalities in health and functioning or vice versa,38 these findings suggest that SEP continues to play a role in the dynamics of ageing until high ages.…”
Section: Discussionmentioning
confidence: 69%
“…For emotional support given and social activity, we found some evidence for a decrease in inequalities over the course of old age. While it is important to note that, on the basis of our analyses, we cannot draw conclusions about whether socioeconomic conditions caused initial inequalities in health and functioning or vice versa,38 these findings suggest that SEP continues to play a role in the dynamics of ageing until high ages.…”
Section: Discussionmentioning
confidence: 69%
“…Similar to other systematic reviews, for example, Kröger et al 36 who consider only studies analysing health selection versus social causation or Niedzwiedz et al 35 who took only studies into account that consider specific life course models and their relation to health, our review follows a conceptual approach by choosing only mediation models. We included all studies that focus on explaining socioeconomic inequalities in SRH, covering at least two of the three main pathways (material, behavioural or psychosocial factors) and analysing the relative contribution of these approaches in separate and joint models.…”
Section: Methodsmentioning
confidence: 99%
“…8 However, the relationship between SEP and health of adults is influenced by processes operating during early life which can impact on their health (and related behaviours) and SEP 4146 50–55 Moreover, childhood SEP may be more important for adult health in certain settings than others, for example, a study found father's education to be more important than own education in explaining differences in self-rated health in Eastern when compared with Western Europe 10…”
Section: Discussionmentioning
confidence: 99%